2016
DOI: 10.1515/oszn-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological air quality at municipal waste sorting plant

Abstract: Municipal waste plants can be a source of biological contamination of the environment, depending on the method of operation and the type of collected waste. The aim of this study was the quantitative characteristics of airborne microorganisms at the Barycz municipal waste sorting plant in Cracow. Bioaerosol measurements of indoor and outdoor air of the municipal waste sorting plant were performed during the summer season using a six-stage Andersen cascade impactor. The highest concentration of bacterial and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…The PSD of fungal aerosol in the WSP was the highest for particles with an aerodynamic diameter of between 3.3 and 4.7 µm in the QSP, and between 4.7 and 7.0 µm in the PSP. Similar results were obtained in a WSP in Cracow, Poland, where the fungal PSD had a maximum peak ranging from 3.3 to 7.0 µm [64].…”
Section: Particle Size Distribution (Psd) Of Isolated Fungisupporting
confidence: 84%
“…The PSD of fungal aerosol in the WSP was the highest for particles with an aerodynamic diameter of between 3.3 and 4.7 µm in the QSP, and between 4.7 and 7.0 µm in the PSP. Similar results were obtained in a WSP in Cracow, Poland, where the fungal PSD had a maximum peak ranging from 3.3 to 7.0 µm [64].…”
Section: Particle Size Distribution (Psd) Of Isolated Fungisupporting
confidence: 84%
“…The size distribution of particles carrying microbial entities in bioaerosols emitted in WSPs has received little attention over the past. Airborne fungal entities were associated with particles < 5 µm in aerodynamic diameters in municipal solid waste treatment plants in Finland [11] and in the range of 3.3-7.0 µm in Poland [17,63]. Thus, results from published studies are contradictory regarding the size of particles carrying microorganisms and are not totally in line with our findings.…”
Section: Size Distribution Of Bioaerosolssupporting
confidence: 53%
“…Knowledge about the taxa composition of microbial communities in bioaerosols from WSPs has been improved through studies using methods based on the identification of cultivated isolates [11][12][13] and based on high throughput sequencing (HTS) [14,15]. In addition, studies have allowed investigation of the size distribution of airborne microorganisms (SDAM) found in the air of WSPs and their deposition in the lungs of workers [16][17][18]. Several studies have also encouraged the completion of the measurement strategy of health effect indicators [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The size distribution could also be influenced by the attachment of fungal particles to other particulate matter [58]. The same results were obtained in a sorting plant in Cracow, Poland where the fungal concentration had maximum values in range of 3.3 to 7.0 µm [45].…”
Section: Resultsmentioning
confidence: 74%
“…The results of the TIMC/m 3 (bacteria and fungi) collected from the sorting plant show that the maximum value was in the PCSP (2626), moreover the high value was obtained in the outdoor air (2366). In a waste sorting plant in Cracow, Poland, the value of TIMC/m 3 in outdoor air was even 61,300 while in indoor 30,490 [45]. Studies carried out in April in a sorting plant located in Korea, showed that the TIMC in indoor air was 21,0000 [38].…”
Section: Resultsmentioning
confidence: 99%